53. PROFESSIONAL CAPACITIES OF SOCIAL WORKERS IN SOME HOSPITALS IN HANOI IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the necessary professional competencies of social workers at 3 major hospitals in Hanoi in 2024: K Hospital, Bach Mai Hospital, and National Pediatric Hospital.Research methods: The cross-sectional descriptive data was collected from 116 medical staffs.Results: Social workers have average competency levels (59.5%), while 22.4% have good competency, and 18.1% have fair competency. Team-based care (61.2%), psychoeducation (64.2%), and case management (54.3%), using the PHQ9 and GAD7 questionnaires (58.6%), and cultural competence (52.6%) are social work skills implemented. However, a warm handoff (71.6%), alcohol and other drug assessment and brief intervention (71.6%), behavioral activation (69.0%), problem-solving treatment (69.8%), and brief cognitive-behavioral therapy (69.8%) are not fully implemented.Conclusions: The study emphasizes the importance of in-depth training and skill enhancement for the social work team to improve healthcare services, and proposes training programs and competency evaluation standards for Vietnamese hospitals.
Keywords: Medical staff; hospital; Hanoi; Social work; professional competency